Impact of a venous thromboembolism prophylaxis "smart order set": Improved compliance, fewer events. Issue 7 (12th June 2013) - Zeidan, Amer M.; Streiff, Michael B.; Lau, Brandyn D.; Ahmed, Syed‐Rafay; Kraus, Peggy S.; Hobson, Deborah B.; Carolan, Howard; Lambrianidi, Chryso; Horn, Paula B.; Shermock, Kenneth M.; Tinoco, Gabriel; Siddiqui, Salahuddin; et al.
<x xml:space="preserve">Abstract</x> Venous thromboembolism (VTE) affects over 700, 000 Americans annually. Prophylaxis reduces the risk of VTE by 60% but many patients still do not receive risk‐appropriate VTE prophylaxis. To improve our institution's VTE prophylaxis performance, we developed mandatory computerized clinical decision support‐enabled "smart order sets" that required providers to assess VTE risk factors and contraindications to pharmacologic prophylaxis. Using provider responses, the order set recommends evidence‐based risk‐appropriate VTE prophylaxis. To study the impact of our "smart order set" on prescription of risk‐appropriate VTE prophylaxis and clinical outcomes, we conducted a retrospective chart review of consecutive patients admitted to the Medicine service during one month immediately prior to (November 2007) and a single month subsequent to (April 2010) order set launch. Data collection included patient demographics, VTE risk factors, and the use and type of VTE prophylaxis. The pre‐ and post‐implementation cohorts contained 1, 000 and 942 patients, respectively. After implementation of the "smart order set", the prescription of risk‐appropriate VTE prophylaxis increased from 65.6% to 90.1% (P < 0.0001). Orders for any form of VTE prophylaxis increased from 76.4% to 95.6% (P < 0.0001). Radiographically documented symptomatic VTE within 90 days of hospital discharge declined from 2.5% to 0.7% (P = 0.002). Preventable harm was completely eliminated (1.1% to 0%, P = 0.001) with no difference in major bleeding or all‐cause mortality. A VTE prophylaxis computerized clinical decision support‐enabled "smart order set" improved prescription of risk‐appropriate VTE prophylaxis, reduced symptomatic VTE and eliminated preventable harm from VTE without increasing major bleeding. Am. J. Hematol. 88:545–549, 2013. © 2013 Wiley Periodicals, Inc.